2016
DOI: 10.1007/s00421-016-3396-9
|View full text |Cite|
|
Sign up to set email alerts
|

Maximal aerobic power and anaerobic capacity in cycling across the age spectrum in male master athletes

Abstract: This file was downloaded from the institutional repository Brage NIH -brage.bibsys.no/nih Capelli, C., Rittveger, J., Bruseghini, P., Calabria, E., Tam, E. (2016 3Methods. In various decades of age (30-80 yy), MAP and AnS were estimated by using an iterative procedure as the 4 values that minimise the difference between: i) the metabolic power (! (t)) necessary to cover a given distance (d) in 5 the time t and; ii) the maximal metabolic power (! max (t)) maintained at a constant level throughout the competiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Age-related declines in endurance and ultra-endurance performance have been well described in the literature for swimming (Tanaka and Seals, 2003; Zamparo et al, 2012; Ferreira et al, 2016; Knechtle et al, 2016), cycling (Balmer et al, 2008; Baker and Tang, 2010; Capelli et al, 2016), running (Leyk et al, 2007; Hoffman, 2008; Hoffman et al, 2010; Knechtle et al, 2012; Lepers and Cattagni, 2012), and triathlon (Baker and Tang, 2010; Bernard et al, 2010; Lepers and Maffiuletti, 2011; Stevenson et al, 2013, Lepers et al, 2013b). The age-related decline in (ultra)-endurance performance with advancing age depends on the discipline and on gender.…”
Section: Performances Of Master Athletes Improved At a Faster Rate Thmentioning
confidence: 80%
“…Age-related declines in endurance and ultra-endurance performance have been well described in the literature for swimming (Tanaka and Seals, 2003; Zamparo et al, 2012; Ferreira et al, 2016; Knechtle et al, 2016), cycling (Balmer et al, 2008; Baker and Tang, 2010; Capelli et al, 2016), running (Leyk et al, 2007; Hoffman, 2008; Hoffman et al, 2010; Knechtle et al, 2012; Lepers and Cattagni, 2012), and triathlon (Baker and Tang, 2010; Bernard et al, 2010; Lepers and Maffiuletti, 2011; Stevenson et al, 2013, Lepers et al, 2013b). The age-related decline in (ultra)-endurance performance with advancing age depends on the discipline and on gender.…”
Section: Performances Of Master Athletes Improved At a Faster Rate Thmentioning
confidence: 80%
“…The PPT was added to quantify cycling performance during XCO-typical load periods of 10 -300 s [3,13,27]. Especially during very high-intensity and maximal efforts (as demanded by PPT), exercise capacity may also be limited by the amount of energy obtained from the anaerobic energy storage [5]. Nevertheless MAP, similar to maximal oxygen uptake (VO2 max ), is one of the most important physiological variables correlated with endurance and maximal performances [16].…”
Section: Discussionmentioning
confidence: 99%
“…Kryger reported that resistance training by women at an advanced age could increase skeletal muscle mass and muscle strength [7]. More recently, the effects of habitual exercise have also been studied [8][9][10].…”
Section: Introductionmentioning
confidence: 99%